Colonic wall injuries after endoscopic resection: still a major complication?: a retrospective analysis of 3782 endoscopic resections - Kouladouros, Konstantinos; Kähler, Georg; Belle, Sebastian (Diseases of the colon & rectum, 2022)
BACKGROUND: - Colonic wall injuries are the most feared adverse events of endoscopic resections among endoscopists. The implementation of endoscopic closure has offered a reliable way to treat such injuries and, thus, has decreased their overall morbidity and mortality. - OBJECTIVES: - The aim of our study is to assess the characteristics and outcomes of colonic wall injuries after endoscopic resection, focusing on the endoscopic treatment of these injuries. - DESIGN: - This was a retrospective cohort study. - SETTINGS: - Patients treated in the Central Endoscopy Unit of the Medical Centre Mannheim were included. - PATIENTS: - We retrospectively analyzed all patients who underwent endoscopic mucosal resection and snare polypectomy in our center between 2004 and 2019 and isolated the resection-related colonic wall injuries. These were divided into 3 groups: group A, endoscopically treated early colonic wall injuries; group B, nonendoscopically treated early colonic wall injuries; and group C, late perforations. - MAIN OUTCOME MEASURES: - Periprocedural factors and treatment outcomes were analyzed and compared among the 3 groups. - RESULTS: - Of 3782 endoscopic resections, we identified 177 cases of colonic wall injuries, of which 148 were identified and treated endoscopically (group A), 9 were identified during the procedure but could not be treated endoscopically (group B), and 20 were late perforations (group C). Endoscopic treatment with use of clips had a technical success rate of 94.3%, while the clinical success rate of technically complete endoscopic closure was 92.6%. Twenty-two percent of all colonic wall injuries required surgical treatment; the type and outcomes of surgery were similar in all groups. Overall hospital stay was significantly lower in group A. - LIMITATIONS: - The main limitation of the study is its retrospective design. - CONCLUSIONS: - Endoscopic closure with the use of clips is a safe and feasible treatment for intraprocedurally identified colonic wall injuries and is associated with significantly decreased necessity of surgery, morbidity, and hospital stay. See Video Abstract at https://links-lww-com.ezproxy.medma.uni-heidelberg.de/DCR/B755. - LESIONES DE PARED COLÓNICA POSTERIOR A RESECCIÓN ENDOSCÓPICA: ¿ES AÚN UNA COMPLICACIÓN IMPORTANTE? ANÁLISIS RETROSPECTIVO DE 3782 RESECCIONES ENDOSCÓPICAS - ANTECEDENTES: - Las lesiones de la pared del colon son los eventos adversos más temidos por los endoscopistas durante las resecciones endoscópicas. La implementación del cierre endoscópico ha ofrecido una forma confiable de tratar tales lesiones y, por lo tanto, disminuyendo su morbilidad y mortalidad general. - OBJETIVOS: - El objetivo de nuestro estudio es evaluar las características y resultados de las lesiones de la pared colónica posterior a la resección endoscópica, centrándose en su tratamiento endoscópico. - DISEÑO: - Es un estudio de cohorte retrospectivo. - ENTORNO CLÍNICO: - Se incluyeron pacientes tratados en la Unidad Central de Endoscopia del Centro Médico de Mannheim. - PACIENTES: - Se analizaron retrospectivamente todos los pacientes sometidos a resección endoscópica de la mucosa y polipectomía en asa en nuestro centro entre 2004 y 2019, seleccionando las lesiones de la pared colónica relacionadas a la resección. Estas se dividieron en tres grupos: Grupo A: lesiones tempranas de la pared colónica tratadas endoscópicamente; Grupo B: lesiones tempranas de la pared colónica no tratadas endoscópicamente; y Grupo C: perforaciones tardías. - PRINCIPALES MEDIDAS DE VALORACION: - Se analizaron y compararon los factores relacionados al procedimiento y los resultados del tratamiento entre los tres grupos. - RESULTADOS: - De 3782 resecciones endoscópicas identificamos 177 casos de lesiones de la pared colónica, de los cuales 148 fueron identificados y tratados endoscópicamente (Grupo A), 9 fueron identificados durante el procedimiento pero no pudieron ser tratados endoscópicamente (Grupo B) y 20 fueron perforaciones tardías. (Grupo C). El tratamiento endoscópico con el uso de clips tuvo una tasa de éxito técnico del 94,3%, mientras que la tasa de éxito clínico del cierre endoscópico técnicamente completo fue del 92,6%. El veintidós por ciento de todas las lesiones de la pared colónica requirieron tratamiento quirúrgico; el tipo y los resultados de la cirugía fueron los mismos en todos los grupos. La estancia hospitalaria global fue significativamente menor en el grupo A. - LIMITACIONES: - La principal limitación del estudio es su diseño retrospectivo. - CONCLUSIONES: - El cierre endoscópico con el uso de clips es un tratamiento seguro y factible para las lesiones de la pared colónica identificadas durante el procedimiento y se asocia con una disminución significativa de la necesidad de cirugía, morbilidad y de estancia hospitalaria. Consulte Video Resumen en https://links-lww-com.ezproxy.medma.uni-heidelberg.de/DCR/B755.